2009
DOI: 10.1253/circj.cj-08-0762
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Thin Cap Fibroatheroma Identified by Virtual Histology and Angioscopic Yellow Plaque in Quantitative Analysis With Colorimetry

Abstract: he major cause of acute coronary syndrome (ACS) is disruption of an atherosclerotic plaque and the subsequent formation of a thrombus. 1 Pathological examinations have revealed that thin cap fibroatheroma (TCFA) is frequently found in patients who die of ACS, and plaque rupture usually occurs in a lesion with an abundant necrotic core and an overlying thin fibrous cap. [2][3][4] Recently, a spectrum analysis of intravascular ultrasound (IVUS)-derived radiofrequency data based on a pathological analysis has d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Intense yellow plaques upon angioscopic examination correlated with the presence of a plaque with a large lipid area on IB-IVUS display 14) . Postmortem histological assessment and in vivo studies with other coronary imaging devices, such as virtual histology IVUS and OCT, have shown that yellow color intensity is associated with a lipid core underneath a thin fibrous cap and that intense yellow plaques might be structurally vulnerable [15][16][17] . Similarly, it has been reported that nonintense yellow plaque was plaque with a thick fibrous cap 17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intense yellow plaques upon angioscopic examination correlated with the presence of a plaque with a large lipid area on IB-IVUS display 14) . Postmortem histological assessment and in vivo studies with other coronary imaging devices, such as virtual histology IVUS and OCT, have shown that yellow color intensity is associated with a lipid core underneath a thin fibrous cap and that intense yellow plaques might be structurally vulnerable [15][16][17] . Similarly, it has been reported that nonintense yellow plaque was plaque with a thick fibrous cap 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Combination study with angioscopy and gray-scale IVUS showed that the presence of yellow plaques is correlated with positive remodeling of coronary arteries 22) . Therefore, intense yellow plaques, which are partly equivalent to thin-cap fibroatheromas identified by OCT or IVUS [15][16][17] , may have a large plaque burden. Also, diffuse long lesions possibly have a large plaque burden since long stent implantation as well as stenting for intense yellow plaques may cause post-procedural myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Their system can consistently measure yellow plaque color independent of such conditions as light intensity, the distance from the lens of angioscope to the objective, and the angle of the angioscope to the region of interest, after proper adjustments for brightness (L * value is within 42) and are strongly correlated with the thin cap fibroatheroma determined by Virtual Histology-IVUS. 43) The plaques of b * value >23 are associated with elevated malondialdehyde-modified low-density lipoprotein levels 44) , which has been reported to be detected in the plasma of patients with ACS.…”
Section: ) Semi-quantitative Evaluationmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] The majority of yellow plaques are composed of lipid-rich tissue or necrotic core identified by optical coherence tomography (OCT) and radiofrequency intravascular ultrasound (IVUS). [10][11][12][17][18][19] In contrast, white plaque is histological fibrous plaque or lipid plaque with thick fibrous cap. 11,[17][18][19] Yellow intensity is negatively correlated with fibrous cap thickness, and intense yellow plaque is corresponded to TCFA.…”
Section: Vulnerable Plaquementioning
confidence: 99%